Seasonal flooding, topography, and organic debris interact to influence the emergence and distribution of seedlings in a tropical grassland - Bao, Francielli [UNESP]; Elsey-Quirk, Tracy; Assis, Marco Antonio de [UNESP]; Arruda, Rafael; Pott, Arnildo (Wiley-Blackwell, 2018)
In seasonally flooded wetlands, inundation and associated organic debris deposition followed by a drawdown period can promote plant community diversity across space and time. Post-flood regeneration might be influenced by the direct effect of flooding on seed dispersal and seedling emergence, as well as the indirect effect of organic debris on seed trapping and germination. Our objective was to examine the influence of seasonal flooding, topography, and organic debris cover on seedling distribution in a seasonally flooded grassland. We measured species richness, seedling abundance, and organic debris cover for 3yr in a seasonally flooded grassland in the Pantanal, Brazil, at three topographic levels at the end of the flood season and during the dry season when there was no debris deposition. A total of 43 species were recorded, with no difference in species richness detected between seasons. However, the abundance of some species was higher post-flood than during the dry period. The greatest seedling abundance and richness were found post-flood at intermediate elevations, followed by high and the lowest elevations. Seed germination and seedling establishment were likely suppressed at low topographic positions due to shading from organic debris and poor drainage. Therefore, areas with predictable annual floods promote diversity by creating spatial and temporal variations in environmental conditions. Resumo Em pastagens sazonais, disturbios naturais como inundacoes e deposicAo de detritos organicos, oferecem varias oportunidades para a regeneracAo das plantas, que podem promover aumento da diversidade das comunidades vegetais ao longo do espaco e tempo. Especificamente, a regeneracAo pode ser influenciada pelo efeito direto das inundacoes na dispersAo de sementes e na emergencia das plantulas, atraves do efeito indireto de detritos organicos na captura e germinacAo de sementes. Nosso objetivo foi examinar a influencia das inundacoes sazonais, topografia e cobertura de detritos organicos na distribuicAo de plantulas em pastagens sazonalmente inundadas do Pantanal. Medimos a riqueza de especies e a abundancia de plantulas por tres anos em tres niveis topograficos com cobertura variavel de detritos pos-inundacAo e seca, neste ultimo, quando nAo houve deposicAo de detritos. Um total de 43 especies foi registrado sem diferenca na riqueza de especies entre as estacoes imediatas pos-inundacAo e seca. No entanto, a abundancia de algumas especies foi maior pos-inundacAo do que pos-seca. A distribuicAo das plantulas diferiu entre os niveis topograficos na pos-inundacAo, com a maior abundancia e riqueza de plantulas no nivel medio, seguido do alto e, finalmente, do nivel baixo, isso se deveu a maior concentracAo de detritos organicos no nivel baixo. Nossos resultados indicam que areas com inundacoes anuais previsiveis promovem a adaptacAo de especies individuais para uma regeneracAo bem-sucedida.
Keywords: Brazil; flooding; neotropical savanna; seedling regeneration; wetland